DIFFERENCE OF STUDENT KNOWLEDGE BEFORE AND AFTER GIVING INFORMATION ON THE HEALTHY AND CLEAN LIFE BEHAVIOR - Husaini Husaini; Nur Laily; Maman Saputra (Lambung Mangkurat, 2015)
AbstractMelayu Elementary School located along the Martapura river has great potential to have students who used to perform daily activities using the river water. Children who live along the river spend their time on the river. This makes them vulnerable to infection of various diseases, either directly through the skin infection when they were playing in the river and indirectly, through drink cooked by their parents are the source of water comes from rivers where they live. The right solution about this conditions that one of them with health education to increase knowledge and awareness of the public. Especially, the children of school age to maintain the clean and healthy lifestyle (healthy and hygiene practices, PHBS). This research is a quantitative research using quasi-experimental approach with one group pre- and post-test design. The study population as much as 49 students, a sample of 29 respondents were determined using purposive sampling technique. Instruments research using questionnaires. Treatment variable is the provision of health promotion information about the behavior of healthy and clean life, while the dependent variable is the knowledge of elementary school students in Melayu Elementary School. Showed as many as two students (6.9%), which still has less knowledge and as many as 27 students (93.1%) who have a good knowledge about PHBS prior to counseling. While the after no more students who have less knowledge or all students (100%) have a good knowledge of PHBS. Based on Wilcoxon test showed that there was no difference in knowledge, before and after counseling. This is because almost all of the students already have a good knowledge prior to counseling so there was no significant difference in the level of knowledge after counseling.Keywords: Education, Knowledge, PHBS